Implementation of the Problem Based Learning Model with Blended Learning on Ecosystem Topics to Enhance Scientific Literacy and Pancasila Student Character - Khoirun Nisa Fesa Nugraheni; Rusilowati, Ani; Marianti, Aditya (Unnes Science Education Journal, 2024)
The Ministry of Education and Culture has changed the national assessment strategy from the National Examination to the Minimum Competency Assessment, Character Survey, and Environmental Survey to address the decline in Indonesia’s PISA ranking. This issue needs to be addressed by implementing a technology-based model that can be applied in education to help students develop scientific literacy skills and character in preparation for AKM and PISA. One of the recommended learning models today is the student-centered learning model, which requires students to actively participate in the learning process, such as Problem-Based Learning with Blended Learning. This study aims to analyze the effectiveness of implementing the blended PBL model in ecosystem material in enhancing students’ scientific literacy and Pancasila student character in the experimental class and to assess the implementation of the PBL model with Blended Learning. This research is a quasi-experimental study. The research design used is the Nonequivalent Control Group Design. The study was conducted at SMAN 1 Kramat, with the research subjects being students from classes X1, X5, X6, and X8.The results showed a significant increase in scientific literacy and Pancasila student character in the experimental class where the blended PBL model was applied to the ecosystem material. The implementation of the blended PBL model was successfully carried out, as evidenced by positive student responses, with 68.86% of the questionnaire scores falling into the good category. Based on the research, it can be concluded that the implementation of the blended PBL model in ecosystem material effectively improves students’ scientific literacy and character can be successfully implemented.